The effect of knowlege management and talent management on employee performance and the impact on competitive advantage (Survey at private colleges in Kulonprogo district, Yogyakarta) - Laras, Titi; Kresnanto, Nindyo Cahyo; Raharti, Rini; Nurwiyanta, Nurwiyanta; Wibowo, Apriyanto Giri (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
This study aims to examine the effect of talent management and knowledge management on employee performance and the impact on performance of Private Colleges Employees in Kulonprogo, Yogyakarta, either partially or simultaneously. The research method used a survey with a questionnaire measured by a Likert Scale. The population is 104 Lecturers and Education Personnel at three active Private Colleges in Kulonprogo District. The data were analyzed by Lisrel 8.80 software. This study produced seven findings. First, Knowledge Management (X1) significantly affects on Employee Performance. Second, Talent Management (X2) significantly affects on Employee Performance (Y). Third, Knowledge Management (X1) and Talent Management (X2) simultaneously have a significant effect on Employee Performance (Y1). Fourth, Knowledge Management (X1) insignificantly affects on Competitive Advantage (Y2). Fifth, Talent Management (X2) insignificantly affects on Competitive Advantage (Y2). Sixth, Knowledge Management (X1) and Talent Management (X2) simultaneously have a positive and significant effect on Competitive Advantage (Y2). Seventh, Employee Performance (Y1) significantly affects on Competitive Advantage (Y2);